THE IMPACT OF PARENTAL INCARCERATION ON CHILDREN IN RESIDENTIAL CHILD CARE: CHALLENGES AND INTERDISCIPLINARY SOLUTIONS - Daněk, Alois (International Journal of Child, Youth and Family Studies, 2025)
Parental incarceration represents a significant challenge for children living in residential child care, exacerbating their psychosocial vulnerabilities and negatively affecting their development. This study, initiated by FICE Czech Republic, examines the prevalence and impact of parental incarceration on children and young adults in Czech residential child care facilities. The research combines data collected through a mixed-methods design with insights gained from the practical operation of a children’s home. The issue is approached not only from an academic perspective but also from the viewpoint of an everyday educator. The quantitative part of the study covered 67 Czech residential child care facilities with a population of over 2,000 children. These findings were contextualized using qualitative data, leveraging my close connection to the researched environment. Among the target group, I identified severe disruptions in social competencies, emotional deprivation, and challenges in trust-building, all linked to parental incarceration. My contribution highlights systemic shortcomings and insufficient interdisciplinary cooperation, among numerous additional challenges. Based on the research findings, I propose necessary modifications, particularly in fostering cross-sector collaboration, implementing targeted prevention strategies, and significantly strengthening support measures. These recommendations aim to support this highly vulnerable group of children and enable them to better cope with the burdens associated with parental incarceration.